Pengembangan Media Pembelajaran Berbasis Flip HTML 5 pada Mata Pelajaran Teknik Pemesinan Bubut di SMK Negeri 1 Padang - Pramudya, Aldhi; Ambiyar, Ambiyar; Nurdin, Hendri; Rahim, Bulkia (MASALIQ, 2024)
Flip HTML 5-based e-modules are a form of presenting material using smartphone and internet technology that can be used as an independent learning resource with a practical and easy-to-operate display. This study aims to analyze the development of learning media based on flip html 5 in lathe machining technique subjects at SMK Negeri 1 Padang. This type of research is development research or also known as R&D (Research and Development). This research uses the ADDIE development procedure. The data collection technique used a questionnaire to obtain information about the quality of the E-Module product developed in the form of a validation sheet. The instrument used by researchers in this development research is a validation guideline. From the results of the validation and practicality questionnaire, it can be concluded that the product based on Project Based Learning in the subject of Lathe Machining class XI Vocational High School is very feasible to use.